2019
DOI: 10.1542/peds.2018-1771
|View full text |Cite
|
Sign up to set email alerts
|

Parent-Adolescent Agreement About Adolescents’ Suicidal Thoughts

Abstract: To examine agreement between parent and adolescent reports of adolescents' suicidal thoughts and explore demographic and clinical factors associated with agreement in a large community sample. METHODS: Participants included 5137 adolescents 11 to 17 years old (52.1% girls; 43.0% racial minority) and a collateral informant (97.2% parent or stepparent) from the Philadelphia Neurodevelopmental Cohort. Families were recruited from a large pediatric health care network. Adolescents and parents completed a clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 87 publications
(41 citation statements)
references
References 37 publications
5
35
0
1
Order By: Relevance
“…We were unable to reach every patient from the research pool for follow‐up, raising the possibility of bias and limiting generalizability. As Jones et al (2019) showed modest agreement between adolescent and parent report of adolescents’ suicidal ideation, it is possible that the use of caregiver report to assess attempts during follow‐up might underestimate our outcome. However, this concern is somewhat mitigated by the fact that the outcome we assessed was not ideation but behavior.…”
Section: Discussionmentioning
confidence: 85%
“…We were unable to reach every patient from the research pool for follow‐up, raising the possibility of bias and limiting generalizability. As Jones et al (2019) showed modest agreement between adolescent and parent report of adolescents’ suicidal ideation, it is possible that the use of caregiver report to assess attempts during follow‐up might underestimate our outcome. However, this concern is somewhat mitigated by the fact that the outcome we assessed was not ideation but behavior.…”
Section: Discussionmentioning
confidence: 85%
“…These patterns in multi-informant reports also have predictive utility: In a recent study of psychiatric inpatient intake assessments, patterns of agreement or disagreement in parent-adolescent reports of adolescent affective symptoms facilitated prediction of treatment outcomes (Makol, De Los Reyes, Ostrander, & Reynolds, 2019). In fact, an emerging body of evidence indicates that informants who vary in their contexts and perspectives provide meaningful information about cross-contextual consistencies in behavior (De Los Reyes, Henry, Tolan, & Wakschlag, 2009; Hartley, Zakriski, & Wright, 2011; Kwon, Kim, & Sheridan, 2012), mental health service use (Jones et al, 2019; Makol & Polo, 2018), and treatment outcomes (Becker-Haimes, Jensen-Doss, Birmaher, Kendall, & Ginsburg, 2017). In sum, research across psychopathology domains, informants, measurement methods, and developmental periods support that multi-informant reporting patterns yield meaningful clinical information.…”
Section: Building An Evidence Base For Selecting Informants: the Opermentioning
confidence: 99%
“…Lifetime suicidal ideation was assessed with the question, ‘Have you ever thought about killing yourself?’ Affirmative responses were followed up with questions about current ideation. Interviewers were trained in a standardized protocol for responding to suicide risk, as described previously (Jones et al, 2019). Lifetime trauma exposure was assessed with eight items assessing exposure to a range of potentially traumatic stressors.…”
Section: Methodsmentioning
confidence: 99%